2020
DOI: 10.1021/acs.chemmater.0c00849
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrochemical Deposition of Transparent Metal Oxide Thin Films from Polyoxometalates

Abstract: Transition metal oxide coatings, owing to their unique combination of optoelectronic, electrochemical, and chemical properties, are at the forefront of functional thin films across diverse technologies. However, achieving uniform and conformal metal oxide thin films of precise nanoscale thickness and optical quality is largely limited to atomic layer deposition methods. Here, we report a direct, fast, solution-based, ambient-condition electrochemical method to deposit transparent thin films of amorphous niobiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Several strategies have been adopted to immobilise the POMs on the surface of the electrode such as drop casting, [11] electrodeposition, [12,13] and entrapment into polymeric matrices, [14,15] layer-by-layer assemblies [16][17][18] and Langmuir À Blodgett films. [19,20] The entrapment into a conducting polymer by use of the electrostatic attraction between POMs (anion) and an oxidized polymer cation is the most common method because of its simplicity, feasibility, room temperature fabrication and adjustable thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies have been adopted to immobilise the POMs on the surface of the electrode such as drop casting, [11] electrodeposition, [12,13] and entrapment into polymeric matrices, [14,15] layer-by-layer assemblies [16][17][18] and Langmuir À Blodgett films. [19,20] The entrapment into a conducting polymer by use of the electrostatic attraction between POMs (anion) and an oxidized polymer cation is the most common method because of its simplicity, feasibility, room temperature fabrication and adjustable thickness.…”
Section: Introductionmentioning
confidence: 99%
“…32,56 An added challenge of alkali niobates is alkali volatility during annealing and crystallizing at high temperature, and excess alkali is often added to mitigate these problems. 55 Spin-coating 57 and electrodeposition 58 of Nb 2 O 5 from TMA 8−x [H x Nb 6 O 19 ] (x−8) (x = 3) were less challenging in previous studies, and much higher Nb concentration solutions are achievable (1.3 M Nb). 57 However, in our previous study, 57 we found that the deposited Nb 2 O 5 films exhibited poor adhesion due to their tendency to crystallize on the substrate (meaning they crystallize as the TMA−POM salt, leading to poor adhesion upon thermolysis to form Nb 2 O 5 ).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Porous POM clusters (ring, wheel, and crown) as inorganic SBUs to construct a POM-based framework endow their integrated pores. As such, POMs, with unmatched physical and chemical properties, are prime candidate SBUs for constructing functional frameworks, covering a wide range of fields among catalysis, luminescence, , medicine, electrochemistry, and energy storage. However, the assembly of purely inorganic POM-based porous frameworks provide the possibility of forming new types of porous materials which incorporate the thermodynamic stability of zeolites and mesoporous silicas with the sophistication and versatility of MOFs . Among the various types of POMs, the ring-like {Mo 36 } cluster should be an ideal SBU for the synthesis of various multidimensional frameworks because of its potential 12 growth points.…”
Section: Introductionmentioning
confidence: 99%